2012
DOI: 10.1155/2012/986978
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Three Adolescent Sexual Health Programs in Ha Noi and Khanh Hoa Province, Vietnam

Abstract: With an increase in sexual activity among young adults in Vietnam and associated risks, there is a need for evidence-based sexual health interventions. This evaluation of three sexual health programs based on the Protection Motivation Theory (PMT) was conducted in 12 communes in Ha Noi, Nha Trang City, and Ninh Hoa District. Inclusion criteria included unmarried youth 15–20 years residing in selected communes. Communes were randomly allocated to an intervention, and participants were randomly selected within e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…That is, self-efficacy had a strong relationship with academic performance and academic achievement. More importantly, previous studies of adolescents in China, Vietnam and Taiwan, who share a similar cultural background with adolescents in South Korea, revealed that HIV prevention self-efficacy increased after HIV prevention education (Kaljee et al, 2005; Lee et al, 2016; Pham et al, 2012). Self-efficacy is an important predictor of healthy behaviours and changes in behavioural intentions in STI high-risk situations (Lee, 2010).…”
Section: Discussionmentioning
confidence: 88%
“…That is, self-efficacy had a strong relationship with academic performance and academic achievement. More importantly, previous studies of adolescents in China, Vietnam and Taiwan, who share a similar cultural background with adolescents in South Korea, revealed that HIV prevention self-efficacy increased after HIV prevention education (Kaljee et al, 2005; Lee et al, 2016; Pham et al, 2012). Self-efficacy is an important predictor of healthy behaviours and changes in behavioural intentions in STI high-risk situations (Lee, 2010).…”
Section: Discussionmentioning
confidence: 88%
“…PMT also has the ability to analyse the current and anticipated pro-environmental behaviours which is extended to drivers and barriers of accepting an adaptive proenvironmental behaviour [30]. The Green IT life cycle [33] are described from manufacturing to disposal including the process of usage in the Figure 2 at every stage including the design stage.…”
Section: Fig 2 Green It Life Cyclementioning
confidence: 99%
“…Youths who attended school-based programs, such as comprehensive sexand HIV-education programs, have been found to have less sexual risk taking and lower pregnancy rates [18]. Several programs have been implemented, such as VFOK (Vietnamese Focus on Kids), the gender-based EWA (Exploring the World of Adolescents) program, and EWA+ (EWA plus parental and health provider education) [19] to improve health literacy of adolescents and parents about the associated sexual risks.…”
Section: Introductionmentioning
confidence: 99%